Correlation and Path Coefficients Analysis for Some Yield Traits in Wheat (Triticum aestivum L.) Genotypes - شيخ, سناء; بولص خوري; مجد درويش (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out in AL- SHEER -LATTAKIA and Tishreen University, during 2020/2021 and 2021/2022 seasons. Five bread wheat (Triticum aestivum L.) genotypes were used L-1300, L-1302,L-68017, L-66233 , L-68467. Half diallel mating method was followed to get 10 hybrids. The hybrids and their parents were sown in the second season, using a randomized complete block design (R.C.B.D), with three replications. Correlations and path coefficient analysis between yield components (number of fertile tillers, spikelet’s spike−1, spike length, Nat Assimilation Rat), flag leaf area), with the individual plant grain yield. Results showed that grain yield had a positive significant correlation (P≤0.01) with each of number of fertile tillers, spike length, spikelet’s spike−1, nat assimilation rat, flag leaf area) (0.8452**، 0.8681**، 0.8950**، 0.8348**، 0.8641**) respectively. Results of path coefficient analysis showed that the direct effect of spike length, number of fertile tillers, nat assimilation rat, on grain yield was high and positive (0.3259, 0.3113, 0.3093) respectively, while the effect was low and positive number of spikelet’s spike−1e on grain yield (0.1203) . Results also showed the indirect effect of nat assimilation rat through spike length had the highest contribution % in yield (16.52%), followed by the indirect effect of number of fertile tillers through spike length in yield (15.661%), the indirect effect of nat assimilation rat through number of fertile tillers (13.234%), then the direct effect of each spike length and of number of fertile tillers (10.621, 9.692%), respectively. The study confirmed the importance of spike length, number of fertile tillers, and nat assimilation rat, as selection indices for high yield in wheat, because of their significant correlation, and high relative importance with yield, either through direct or indirect effects